Global prevalence and dynamics of mecA and mecC genes in MRSA: Meta-meta-analysis, meta-regression, and temporal investigation - Adeiza Shuaibu Suleiman; Prosun Bhattacharya; Md. Aminul Islam (Journal of Infection and Public Health)
This study aimed to conduct first robust meta-meta-analysis on mecC and mecA-positive MRSA strains, determining their overall prevalence and temporal trends. It encompassed 14 meta-analyses, involving 322,269 samples from 553 index studies. MRSA strains exhibited mecA / mecC positivity ranging from 0.90 % to 69.98 %. Varied AMSTAR and QUOROM scores were observed. mecC-positive MRSA prevalence was 2.41 % (95 % CI: 0.72–7.78 %). Human mecA-positive MRSA had 21.77 % prevalence (95 % CI: 9.08–43.67 %), animal samples had 7.08 % prevalence (95 % CI: 3.93–12.42 %), and worldwide prevalence was 14.58 % (95 % CI: 6.61–29.14 %). Temporal trends reveal fluctuations, mecA prevalence spiked to 52.68 % in 2012 and decreased to 7.11 % in 2022. For mecC gene, the year 2015 marked a low incidence of 0.41 % (95 % CI: 0.05–3.54 %). Overall, mecA gene carriage surpassed mecC in MRSA strains, especially in humans.